Transfer pricing of innovation considering matches between innovation and technology in firms - Liu, Huihong; Liu, Xinyu; Balezentis, Tomas; Streimikiene, Dalia; Zeng, Shouzhen (Journal of Business Economics and Management, 2023)
Firms can purchase innovation results to improve their technology. In this context, the key to transfer success is reasonably priced innovation results. Considering the match between innovation results and firm technology, this study analyzes the nonlinear improvement effect of innovation results on technology. The pricing decision is then assessed by a game model of the innovation results transfer and pricing that is based on the entire innovation process, including research and development (R&D) and transfer. Then the method for transfer pricing of innovation results is obtained from the equilibrium of game. The results show that firms tend to evaluate innovation results by matching them with their own technologies, and then make bids based on the R&D costs. Here, innovation results are obtained by firms with high-level matching. After considering the matching, the transfer pricing of innovative results will prosper the transfer market and improve the success rate of transfer. Several factors affect the possibility of transfer of innovation results and their price, including the R&D ability of the institution, the technology levels of firms, and the technological competition between firms. These conclusions were validated using a numerical example.